Photochemistry of PSII in CYP38 Arabidopsis thaliana deletion mutant - Lepeduš, Hrvoje (Array, 2009)
Summary: Chloroplast protein CYP38 is a cyclophilin-like peptidyl-prolyl cis-trans isomerase involved in photosystem II (PSII) assembly. It also serves as a regulator of thylakoid protein phosphatase. In this work the efficiency of PSII in CYP38 deficient Arabidopsis thaliana M13 plants has been analyzed by measuring in vivo chlorophyll a (Chl a) fluorescence transient (OJIP test). Significant differences in overall photosynthetic performance (PIABS), absorption (ABS/RC), trapping (TRo/RC), electron transport (ETo/RC), and dissipation (DIo/RC) were observed between A. thaliana M13 and the wild type (WT) plants. Increased Chl a and Chl b levels, as well as decreased Chl a/Chl b ratio were measured in M13 plants, indicating the adjustment of PSII antenna for increasing light absorption capability. Based on the obtained results, it can be concluded that the deficiency in CYP38 protein leads to impaired function of PSII due to the conversion of a certain fraction of active reaction centres to dissipative ones. This leads to a decrease in overall photosynthetic performance (PIABS) in M13 plants. Such effect was due to lowering of TRo/DIo parameter, which was influenced mostly by significant increases in energy dissipation (DIo/RC) and in trapping of electrons (TRo/RC) per active reaction centre